Analisis optimasi topologi desain support bracket pada steering main shaft mobil TITEN EV-2 - Dinasti Achmad Tristanto; Santoso Mulyadi; Muh. Nurkoyim Kustanto; Agus Triono; Intan Hardiatama (Universitas Muhammadiyah Metro, 2023)
The KMHE competition which focuses on optimizing energy in developing cars is held as a form of contribution to overcoming the problem of dwindling energy sources. To get a cell phone with low energy consumption, one alternative is to design a cell phone as often as possible. This research examines the effectiveness of topology optimization methods in making lightweight component designs while maintaining the ability to accept loads when applied. The components that are being optimized are the support brackets on the main shaft steering of Car TITEN EV-2 which are produced using additive manufacturing with PLA+ materials. The load borne by the design is the load when the car is braking and turning. Two Topology Optimization experimental methods were carried out based on the loading arrangement. The first method is carried out by combining two topological optimization results based on loading to produce the final design. The second method is carried out by applying the two loadings simultaneously to the TO process. As a result, the second TO method showed very good results compared to the first method and was redesigned to produce a new design that was ready for use. The results of the new design have a mass of 34.25% lower than the original design. The FEA simulation results also show the results of increasing design strength after topology optimization. The maximum von-mises voltage drop of the new design in the case of braking, turning and combined loading (braking and turning) respectively is 12.56 MPa, 11.64 MPa and 17.99 MPa compared to the original design which is 30.16 MPa, 26.19 MPa and 51.9 MPa.